How humans evolved according to grade 12 students in Singapore. Issue 2 (24th June 2015) - Seoh, Kah Huat Robin; Subramaniam, R.; Hoh, Yin Kiong
Abstract: Tree thinking, the understanding of the evolutionary relationships between organisms depicted in different types of tree diagrams, is an integral part of understanding evolution. Novice learners often read tree diagrams differently from specialists, resulting in diverse interpretations of the relationships depicted. The aim of this study is to understand how learners construct the picture of human phylogeny, focusing particularly on their views of the last common ancestor of two sister species, humans, and chimpanzees. A theoretical framework based primarily on the schema theory is used to interpret these views. The primary study gathered responses to an open‐ended question about human ancestry at various time points in our evolutionary history. The data were coded into categories consisting of lineage, trait description, trait gain, trait loss, and others . The lineage responses were further categorized and examined in the secondary study, with the provision of a simplified phylogenetic tree and the main lineage responses obtained in the primary study. Thirteen students were also selected for interviews. Diverse interpretations, including those that consider humans as direct descendants of extant apes (transmutation) or products of hybridization between extant apes, were found to be affected by respondents' alternative schemata related to the last common ancestor and deep time . We also discuss the potential influence of religious and cultural worldviews on some of these interpretations and present nine alternative models of how learners visualize the last common ancestor that humans shared with the chimpanzee. Findings suggest that complex interactions between different sets of schemata (consilience) may result in diverse interpretations of simple phylogenetic trees. Implications for the teaching of tree thinking are provided. © 2015 Wiley Periodicals, Inc. J Res Sci Teach 53: 291–323, 2016.